Nilai Tukar Petani : Konsep, Pengukuran dan Relevansinya sebagai Indikator Kesejahteraan Petani - Muchjidin Rachmat (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2013)
EnglishThe purpose of development is improving welfare of the community such that in every stage of development the welfare of society is always prioritized. Indonesia as an agrarian country with a large population and the dominant proportion of rural farm households prioritizes farmers’ welfare as a strategic issue. One of the farmers’ welfare survey tools is Farmers’ Terms of Trade (FTT). FTT is the ratio of prices received by farmers to the price paid by farmers. This concept simply reflects the purchasing power of farmers’ income. However, the concept based on the computation of FTT fixed quantity (Laspeyres index) does not fully describe the indicator of the farmers’ welfare. The increase in product prices received by farmers is equal to an increase in farmers' income. The increase in prices received by farmers indicates the scarcity of agricultural production supply. FTT measurement also does not accommodate productivity growth, technological progress and development improvement. Thus, improvement for computing FTT is necessary by incorporating elements of quantity so that FTT value is income to expenditure ratio. The simplest way is computing the Agricultural Production and the Household Consumption indices for FTT. Another improvement is to refine the scope of agricultural farmers defined in the FTT computation. IndonesianTujuan pembangunan adalah peningkatan kesejahteraan masyarakat, sehingga dalam setiap tahapan pembangunan kesejahteraan masyarakat selalu menjadi tujuan utama. Sebagai Negara agraris dengan jumlah penduduk besar dan proporsi rumah tangga yang bekerja di pertanian dominan, maka perhatian terhadap kesejahteraan petani dinilai sangat strategis. Salah satu alat ukur kesejahteraan petani yang digunakan saat ini adalah Nilai Tukar Petani (NTP). NTP dihitung dari rasio harga yang diterima petani (HT) terhadap harga yang dibayar petani (HB). Konsep ini secara sederhana menggambarkan daya beli pendapatan petani. Namun konsep penghitungan NTP yang didasarkan kepada kuantitas yang tetap (indeks Laspeyres) belum sepenuhnya merupakan indikator kesejahteraan petani. Kenaikan harga produk yang diterima petani tidak identik dengan peningkatan pendapatan petani. Kenaikan harga yang diterima petani justru mengindikasikan kelangkaan suplai/produksi pertanian. Konsep pengukuran NTP juga tidak mengakomodasikan perkembangan produktivitas, kemajuan teknologi dan pembangunan. Dalam kaitan sebagai indikator kesejahteraan petani, penyempurnaan penghitungan NTP perlu dilakukan melalui pendekatan nilai yaitu dengan memasukkan unsur kuantitas sehingga NTP merupakan rasio antara nilai pendapatan terhadap nilai pengeluaran. Cara paling sederhana adalah dihitungnya Indeks Produksi Pertanian dan Indeks Konsumsi Rumah tangga petani dalam penghitungan NTP. Penyempurnaan lain adalah menyempurnakan cakupan petani sesuai definisi pertanian dalam perhitungan NTP.